(untitled) (Aporte Santiaguino, 2025)
Climate change has gained increasing importance in scientific research worldwide, particularly regarding its impact on water resource availability and management. In this context, various hydrological models have been employed to estimate the water balance with greater accuracy. Among them, the Soil and Water Assessment Tool (SWAT) has stood out for its ability to simulate hydrological processes under different climate scenarios. The objective of this study was to conduct a systematic review of the use of the SWAT model as a tool to assess water balance in the context of climate change in Peru, during the period from 2019 to 2024. The methodology followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, allowing for a rigorous and structured search of scientific literature in the Scopus, ScienceDirect, and SciELO databases. A total of 41 articles were identified and analyzed: 39 from Scopus, 2 from ScienceDirect, and none from SciELO. The results show that the SWAT model has been widely used in different types of watersheds across the country, demonstrating high adaptability to diverse geographic conditions and data availability. It is concluded that the SWAT model is a robust and reliable tool for estimating water balance under climate change scenarios, and it can support the sustainable management of water resources in Peru.